2017
DOI: 10.17576/akad-2017-8701-05
|View full text |Cite
|
Sign up to set email alerts
|

Pengalaman Sokongan Sosial Intergenerasi dalam Kalangan Warga Emas di Institusi Kebajikan Awam

Abstract: ABSTRAK Sokongan sosial intergenerasi antara anak dewasa dan ibu bapa tua merupakan fenomena yang menjadi

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 9 publications
(11 reference statements)
0
6
0
3
Order By: Relevance
“…Moreover, a study conducted by Baharuddin and Ismail (2013) found that the elderly needs to be empowered spiritually, physically and mentally, followed by appointment as advisors to the younger generation with the aim of producing positive and successful intergenerational relationships (Mohamad et al, 2017). This is in conformity with studies carried out by Ismail et al (2017); Siren (2015) that demonstrate five components required by the elderly namely: (i) Motivation, (ii) Shelter, (iii) Spirituality, (iv) Encouragement of love and (iv) Safety.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Moreover, a study conducted by Baharuddin and Ismail (2013) found that the elderly needs to be empowered spiritually, physically and mentally, followed by appointment as advisors to the younger generation with the aim of producing positive and successful intergenerational relationships (Mohamad et al, 2017). This is in conformity with studies carried out by Ismail et al (2017); Siren (2015) that demonstrate five components required by the elderly namely: (i) Motivation, (ii) Shelter, (iii) Spirituality, (iv) Encouragement of love and (iv) Safety.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Ini bermakna Malaysia telah dikategorikan sebagai negara emas dalam tempoh 4 tahun lagi. Statistik JKMM 2014 menunjukkan terdapat seramai 1,850 orang warga emas di 11 institusi penjagaan kerajaan dan 4,968 orang warga emas di 186 buah institusi penjagaan di bawah Pertubuhan Bukan Kerajaan dan swasta seluruh Malaysia (Nurhayati et al 2017).…”
Section: Tinjauan Literaturunclassified
“…Pekerja sosial di institusi penjagaan juga kurang diberi pendedahan mengenai aktiviti GRT untuk warga emas demensia di institusi. Selain itu, pekerja sosial gerontologi di Malaysia masih lagi kurang dan tiada aktiviti khusus untuk warga emas demensia di institusi penjagaan (Khadijah 2012& Nurhayati et al 2017.…”
Section: Tinjauan Literaturunclassified
See 1 more Smart Citation
“…The global population of the elderly increases every year (Lu, Kao, & Hsieh, 2010). There is an estimated 703 million elderly around the world as of mid-2019 However, the increase in the population of the elderly in Malaysia has a significant impact on the society and country, especially from their acceptance will lead to attitude because they are mainly will take care of this community (Mohamad, Alavi, Mohamad, & Aun, 2017). Attitude is an evaluation of someone or something on a continuum of like or dislike (Doherty, Mitchell, & O'Neill, 2011), consisting of three components, namely affective, cognitive, and behavioural (Soderhamn, Lindencrona, & Gustavsson, 2000).…”
Section: Introductionmentioning
confidence: 99%